The Phenomenon of Masculinity and Femininity Between the Arabic and Kurdish Languages - A Comparative study (Raparin Journal of Humanities (RJH), 2021)
The clarity of the expressions or utterances to a listener in a discourse depends on to what extent the speaker or writer is accurate. Using masculinity and femininity indicates the intention of the speaker or writer more precisely. Therefore, the speaker should choose appropriate grammatical gender category for the pronouns, possessive pronouns and demonstrative pronouns and take some other matters that must be present for being accurate. The languages are divers in terms of masculine and feminine phenomenon. There are some languages which apply gender in parts of speeches, known as beautiful languages, while others apply the gender rules in some specific ways and situations. Therefore, studying gender phenomenon is crucial in two languages, classical Arabic language and Kurdish language (Northern Kurdish), within the same language family. The distinctions and similarities of gender phenomenon of both languages should be dealt with so as to help the learners of both languages. This can be considered as one of the main objectives of contrastive studies. This paper aims at investigating the gender morphemes and linguistic structures of gender in Arabic and Kurdish languages by analyzing and clarifying expressions, sentences, demonstratives and pronouns. This paper consists of two main sections: the first one is devoted for nouns from Arabic and Kurdish languages in term of gender while the second one is dedicated for studying gender phenomenon (masculinity and femininity) from Arabic and Kurdish expressions.